Malignant epithelioid peripheral nerve sheath tumor with prominent reticular/microcystic pattern in a child: a low-grade neoplasm with 18-years follow-up - Agaimy, Abbas; Stachel, Daniel; Jüngert, Jörg; Radkow, Tanja; Carbon, Roman; Metzler, Markus; Holter, Wolfgang (Applied Immunohistochemistry & Molecular Morphology, 2014)
Malignant peripheral nerve sheath tumors (MPNSTs) constitute <2% of soft tissue neoplasms in children and display a wide histologic spectrum including low-grade and epithelioid variants, although most are high-grade spindle cell sarcomas. Here, we describe an unusual case of a large retroperitoneal epithelioid MPNST diagnosed in a 7-year-old girl without family history or clinical features of neurofibromatosis type 1. The patient was treated by repeated surgical interventions, polychemotherapy, autologous stem cell transplantation, and irradiation therapy. Over the years, she developed multiple disseminated abdominal recurrences but is currently alive with very slowly progressing disseminated intra-abdominal disease 18 years from initial diagnosis. Histologically, the tumor was composed of medium-sized polygonal and ovoid-to-spindled cells set within a copious myxoid matrix with a prominent reticular and microcystic pattern reminiscent of the recently described reticular/microcystic schwannoma. Immunohistochemistry revealed strong and diffuse expression of S100, CD56, CD57, collagen IV, and neuron-specific enolase, with negativity for perineurial cell markers (claudin-1, epithelial membrane antigen, and glucose transporter-1) and other lineage-specific mesenchymal and epithelial antigens. This unusual variant of low-grade MPNST must be differentiated from a variety of other entities, in particular benign perineurioma, myxoid neurofibroma, and benign reticular/microcystic schwannoma. Confinement of the recurrent disease to the abdominal cavity emphasizes the necessity of primary curative wide excision of this highly recurring but nonmetastasizing low-grade neoplasm.
EVALuna2:6527